2014
DOI: 10.1530/rep-13-0560
|View full text |Cite
|
Sign up to set email alerts
|

PKA and CaMKII mediate PI3K activation in bovine sperm by inhibition of the PKC/PP1 cascade

Abstract: To enable fertilization, spermatozoa must undergo several biochemical processes in the female reproductive tract, collectively called capacitation. These processes involve protein kinase A (PKA)-dependent protein tyrosine phosphorylation including phosphatidylinositol-3-kinase (PI3K). It is not known how PKA, a serine/threonine (S/T) kinase, mediates tyrosine phosphorylation of proteins. We recently showed that inhibition of S/T phosphatase 1 (PP1) causes a significant increase in phospho-PI3K. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 58 publications
2
26
1
Order By: Relevance
“…In PC12 cells, Ca 2þ entry triggers both Pyk2 activation and cytonuclear accumulation, and the Ca 2þ -dependent Ser/Thr phosphatase calcineurin is required for these effects (Faure et al, 2007). The role of protein kinase A (PKA) and protein phosphatase 1(PP1) has also been suggested (Battistone et al, 2014;Park et al, 2000;Rotfeld et al, 2014) {Park, 2000Battistone, 2014 #808;Rotfeld, 2014 #807}. Pyk2 contains several putative (de)phosphorylation sites for these kinases and phosphatases, mainly located in the kinase-FAT linker (Oppermann et al, 2009) {Oppermann, 2009 Thus, Pyk2 appears to be able to detect multiple signals triggered by Ca 2þ .…”
Section: Conserved Mechanism Despite Differences?mentioning
confidence: 99%
“…In PC12 cells, Ca 2þ entry triggers both Pyk2 activation and cytonuclear accumulation, and the Ca 2þ -dependent Ser/Thr phosphatase calcineurin is required for these effects (Faure et al, 2007). The role of protein kinase A (PKA) and protein phosphatase 1(PP1) has also been suggested (Battistone et al, 2014;Park et al, 2000;Rotfeld et al, 2014) {Park, 2000Battistone, 2014 #808;Rotfeld, 2014 #807}. Pyk2 contains several putative (de)phosphorylation sites for these kinases and phosphatases, mainly located in the kinase-FAT linker (Oppermann et al, 2009) {Oppermann, 2009 Thus, Pyk2 appears to be able to detect multiple signals triggered by Ca 2þ .…”
Section: Conserved Mechanism Despite Differences?mentioning
confidence: 99%
“…PP1 is a key regulator of CaMKII, which functions as a serine/ threonine kinase by autophosphorylation at its threonine-286 through the inhibition of PP1, leading to the regulation of synaptic strength in forebrain postsynaptic density (Strack et al, 1997a;Blitzer et al, 1998;Baucum II et al, 2012) and mediates PI3K activation in bovine sperm capacitation (Rotfeld et al, 2014). Furthermore, the dephosphorylation of CaMKII in postsynaptic density was previously shown to be catalyzed by PP1 (Shields et al, 1985;Dosemeci and Reese, 1993;Strack et al, 1997b).…”
Section: Threonine-290 Regulates Human Pxr Nuclear Translocationmentioning
confidence: 99%
“…It has also been shown that CaMKII negatively regulates SSH1L activity by phosphorylation/activation of LIMK1, which regulates the subcellular localization of SSH1L (Zhao et al 2012). In our recent study, we show that CaMKII activates Pyk2 leading to PI3K phosphorylation/activation in sperm (Rotfeld et al 2014), and it has been shown elsewhere that PI3K mediates the activation of SSH1L (Nishita et al 2004). Thus, it is possible that activation of CaMKII/ PI3K cascade during sperm capacitation together with the increase in [Ca 2+ ] i activates SSH1L which dephosphorylates p-cofilin towards the end of the capacitation process.…”
Section: Discussionmentioning
confidence: 59%